Two fundamental constants of gravity unifying dark matter and dark energy - V. G. Gurzadyan; A. Stepanian (European Physical Journal C: Particles and Fields, 2018)
Abstract The common nature of the dark sector—dark energy and dark matter—as shown in Gurzadyan (arXiv:1712.10014, 2017) follows readily from the consideration of the generalized Newtonian potential as a weak-field version of General Relativity. The generalized potential satisfying Newton’s theorem on the equivalence of sphere’s gravity and that of a point mass located in its center contains an additional constant, which along with the gravitational constant is able to explain quantitatively both dark energy (the cosmological constant) and dark matter. So, gravity is defined not by one but two fundamental constants. We show that the second constant is dimension-independent and matter-uncoupled and hence is even more universal than the gravitational constant, thus affecting the strategy of observational studies of dark energy and of the search of dark matter.